Diagnosis and Tolerant Control Methods for an Open-Switch Fault in a Vienna Rectifier - Park, Jin Hyuk; Lee, June Seok; Kim, Myung Yong; Lee, Kyo Beum (IEEE Journal of Emerging and Selected Topics in Power Electronics, 2021)
In this article, fault diagnosis and tolerant control methods are proposed for an open-switch fault in a Vienna rectifier. The proposed diagnosis method uses only the input currents to detect an open-switch fault without any additional hardware. In the proposed tolerant control, the offset voltage is used to restore the input currents when an open-switch fault occurs in a Vienna rectifier. In addition, the proposed tolerant control considers the balance of the neutral-point voltage. This method can improve the total harmonic distortion (THD) of the current and mitigate the dc-link voltage ripple. The effectiveness of the proposed open-switch fault diagnosis and tolerant control method is verified by simulated and experimental results.
Keywords: Control methods; Dc link voltage ripple; Diagnosis methods; Neutral-point voltages; Offset voltage; Open switch fault diagnosis; Total harmonic distortion (THD); Vienna rectifiers; Open-switch circuit; open-switch diagnosis; open-switch fault; open-switch fault tolerant control; Vienna rectifier